P. 1
Geometric Progression

Geometric Progression

|Views: 19|Likes:
GEOMETRIC PROGRESSION
GEOMETRIC PROGRESSION

See more
See less

07/26/2014

pdf

text

original

Geometric Progression A sequence is said to be in Geometric Progression, if the ratio between any two adjacent numbers in the sequence

is constant (non zero). This constant is said to be common ratio (c.r.) e.g. 1, 2, 4, 8 ..........…… 1, 1/2, 1/4, 1/8, …..……… 1/4, –1/2, 1, –2, 4, ……… In general a, ar, ar2, ar3, ……, a rn–1 By close inspection of the above series we can say the n-th term of GP will be given by tn = arn–1 c.r. = 2 c.r. =1/2 c.r. = –2

Sum of a geometric progression Now, let us try to find out the sum of the first n terms of a G.P. Sn = a + ar + ar2 +…+ arn–1 … (6) Multiplying both sides by r, we get, rSn = ar + ar2 +…+ arn–1 + arn … (7) Subtracting (7) from (6), we have Sn – rSn = a – arn or, Sn = a(1–rr)/(1–r) … (8) From equation (8) sum of n terms of a G.P. Sn = a(1–rr)/(1–r) Basically we have to find out the value of particular case when, n tends to infinity.

b3.If we take any value of |r| greater than 1 then value of rn when n → ∞ will tend to infinite.P. a2. . a2b2. .. Are you getting convinced that it will tend to infinity. multiply and divides to each term of a geometric series? 1. If we take of |r| less than rn when n → ∞ will tend to zero. a3. …….r.’s also results a G. Suppose a1. (take any number greater than 1 multiply it by itself several time. α.P. an are in G.P.P.P. a3. Note: Students are suggested to assume the known variable related to geometric progression in following way. . Multiplication/Division of two G. ka2. Suppose a1. ……. αß Four number in G.P.P. Suppose a1.P. anbn then a1/b2. a3. ……..r = ß c. a1 will also be in G.P. then 1/a1. an are in G. . 3. then a1b1.. a2. 1/an will also be in G. Where k ? R and k ≠ 0. then ka1. also results a G. Multiplication/Division by a constant number to each term of a G. = ß2 .’s also results a G. ∴ α/ß. ... αß3 c. an/k will also be in G. ……. a2/k. 2. b2. Three number in G. Thus S∞ = a/1–r for |r| < 1 … (9) Enquiry : What happens when any real number can be add subtract.P. an/bn will also be in G. 4. a2.. then an. Reversing the order of a G. a2. a2. ka3. a3. α ß. Taking the inverse of a G. a3. a3b3. …….P. Do the same exercise with one another number less than 1). ……. kan and a1/k.. an–1. an and b1.P. ..P.P.. a2/b2. αß. …….P. Suppose a1.P. 1/a2... …….P.. ∴ α/ß3. an–1. an are in G.P. bn are two G. 1/a …….. also results a G. Hence value of S∞ will also tend to infinite.

ark in case we have to take (2k + 1) terms in a G.. we take a/rk.. a2. then the resulting sequence is also a G. an are in G. • If a1. ar3. …….P. …. …. a2. it is convenient to take them as a/r.. . …… is also a G. αß . a.. b3. in case we have to take 2k terms in a G. • If a1. • If we have to take four terms in a G. a3b3. b1. a2. …… is a G. a. . then loga1.P.P. with common ratio rk. is multiplied (or divided) by a fixed non-zero constant.Five numbers in G. = ß Summary of Important Notes: • If each term of a G. • If each term of a G. b2. with same ratio as that of the given G. ……. ∴ α .P. a G b are in G. a3. In general.P. ar. ar..’s with common ratios r and r’ respectively then the sequence a1b1. loga2. with common ratio rr’. a/r. a3. G be the geometric mean between two number a and b So. then middle one is said to be geometric mean (GM) of two others.P.P.P.r. ……. or. it is convenient to take them as a/r3. G2 = ab ∴ G =√ab Similarly we can find two geometric means between two given numbers a and b.P. a2b2. loga3 …… is an A. then a1an = a2an–1 = a3an–2 = …… • If a1. a/r. G/a = b/G.P.P. (with common ratio r) is raised to the power k. then the resulting sequence is also a G. we take a/r2k–1. a/r2k–3. αß2 – c. In general. • If we have to take three terms in a G.. .P.P.P.. ar.P..P..P. Let. Geometric mean between two numbers If three numbers are in G. …… are two G. (each a1 > 0). ar. . The converse is also true. a/rk–1. ar2k–1.

G1.M. b. Solved examples based on GP Solved examples : Illustration: The 7th term of a G. So if a. is 3. Also t5 = 48 Þ ar4 = 48 or 16a = 48 ⇒ a = 3. …….Let a. Gn b will be a G. then b = √ac is the geometric mean of a and c. Solution: Given that t7 = 8t4 ⇒ ar6 = 8ar3 ⇒ r3 = 8 = 23 ⇒ r = 2.. then their G. G2. when its 5th term is 48. • If a1.P. 12. G1. 6. 24 …… Illustration: . a2.P. tn = a rn–1 or b/a = r3 r =(b/a)1/3 G1 = ar2 = a (b/a)1/3 = a1/3 b2/3 Geometric Mean(s) • If three terms are in G. c are in G..…. Hence the required G. ⇒ r = n+1√b/a ⇒ G1 = an+1√b/a. Find the G.(G) is given by G = (a1a2a3. Here b = arn+1.P. an)1/n.P. an are non-zero positive numbers. ……. is 8 times the 4th term.P. b are in G. then the middle term is called the geometric mean (G. Gn = a(n+1√b/a)n. G2. G2. G2 = a(n+1√b/a)2.P.M. ……. …… Gn are n geometric means between and a and b then a. If G1.) between the two.P.

An arithmetic-geometric progression is of the form ab. because common difference is given. Arithmetic-Geometric Progression Suppose a1. …… is a G. …. whose first term is A and common ratio is R. Hence there are infinite numbers of G. 27 = ARt–1 ⇒ 8/12 = Rm–n = 2/3.P.P. a3. 8/27 = Rm–t =(2/3)3 ⇒ 2m – 2n = n – t and 3m – 3n = m – t ⇒ 2m + t = 3n and 2m + t = 3n ⇒ 2m+t/3 = n. –4. Solution: This is very tricky question. 12/27 = Rn–t = (2/3)2. anbn is said to be an arithmetic-geometric progression. is (a–6)2 = a(a+6) or. a2. For example. b3. (a+d)br. how many such progressions are possible? Solution: Let 8 be the mth. If you read question carefully then it is clear that we have to start with A.P. a–6.P. a2 – 12a + 36 = a2 therefore numbers are 8. …… Its sum Sn to n terms is given by . Then 8 = ARm–1. b2. Then the sequence a1b1. 12 the nth and 27 be the tth terms of a G. and b1. 12 = ARn–1. Illustration: In a four term series if first three are in G. (a + 3d)br3. a2b2. There are infinite sets of values of m. n. 12 (not consecutive).P. and last three are in A.P. Let the numbers be a + 6.P. with common different 6 and last terms is equal to the first term then find all four terms in series. …. then 2+t/3 = n = k ⇒ n = k.Does there exists a G. a. a+6 now first three are in G.P. 8. take m = 1.’s whose terms may be 27. By giving different values to k we get integral values of n and t. t which satisfy this relation.P. containing 27. 8. (a + 2d)br2. t = 3k – 2. 8 and 12 as three of its terms? If it exists. 2. is an A.

Solution: Let S = 1.22 + 3.22 + 1.23 +…+ 100.2100 + 100. consider n (1/2)r for increasing value of n i.5 …… (1) …… (2) .Sn = ab + (a+d)br + (a+2d)br2 +……+ (a+(n–2)d)brn–2 + (a+(n–1)d)brn–1. Illustration: Let r = 1/2. 22 + 3 .2 + 2. the sum of the infinite number of terms of the progression is limn→∞ Sn = ab/1–r + dbr/(1–r)2.2 (2100–1/2–1) – 100.23 +…+ 99.2101 ⇒ –S = 1.2 + 1.22 + 2.23 +…+ 1. 22 +…+ 100 . 2 + 2 . Solution: n = 1 : 1. Multiply both sides by r. 2100.2101 ⇒ –S = 1.2101 = 199. (1/2)1 = 1/2 = 0.2101 ⇒ S = –2101 + 2 + 100. Arithmetic Geometric Progression Solved Examples Illustration: Find the sum of series 1 . = ab + dbr(1–rn–1)/(1–r) (a+(n–1)d)brn ⇒ Sn = ab/1–r + dbr(1–rn–1)/(1–r)2 – (a+(n–1)d)brn/1–r.2100 ⇒ 2S = 1.e. Subtracting we get (1 – r)Sn = ab + dbr + dbr2 +…+ dbrn–2 + dbrn–1 – (a+(n–1)d)brn.2100 – 100.2101 + 2. so that rSn = abr+(a+d)br2+…+(a+(n–3)d)brn–2+(a+(n–2)d)brn–1+(a+(n–1)d)brn. If –1 < r < 1.

P. tm–1. Solution: Let S = 1 + 4/5 + 7/52 + 10/53 + ……… 1/5 S = 1/5 + 4/52 + 7/53 ……… Subtracting (1–1/5) S = 1 + 3/5 + 3/52 + 3/53 + ……… 4/5 S = 1/1–3/5 (? It is infinite G.P.) ⇒ S =25/8 Illustration: Let t1. 88. 33. be a sequence so that (i) tm+1/tm = tm/tm–1 ……… constant then tp = (t1)rp–1 (r) (ii) tm+1/tm = tm/tm–1 = constant (r) then tp = constant 1 + (constant 2) × rp–1 (iii) If the difference of difference of terms are in G. 14. then tp = a + bp + crp–1. t3.n = 2 : 2 × (1/2)2 = 1/2 = 0.5 n = 3 : 3 × (1/2)3 = 0. where r is the common ratio.00976. Illustration: 7. 738 ………… Note: . Illustration: Evaluate 1 + 4/5 + 7/52 + 10/53 +…… to infinite terms. ……. and so on Thus we observe that as n → ∞ n rn → 0 for |r| < 1. 251. tm. t2.375 n = 10 : 10 (1/2)10 = 0. tm+1.

we get a = 3.324/108 = 108/36 = 36/12 = 3 ∴ tp = a + bp + c 3p–1 p=1 t1 = 7 = a + b + c p=2 p=3 t2 = 14 = a + 2b + 3c t3 = 33 = a + 3b + 9c Solving. c = 3 ⇒ tp = 3 + p + 3. (3p–1) . b = 1.

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->